A Hybrid Mom/FEM Technique for Scatter from a Complexe BOR with Appendages - Greenwood, Andrew D. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A hybrid technique is developed to allow the scattering from small appendages to be approximately combined with the scatter from a large body of revolution (BOR). The hybrid technique thus enables the rotational symmetry of the large BOR to be exploited to solve the scattering problem with much less computational complexitity than a fully three-dimensional (3-D) solution. The technique combines the finite element method (FEM) for BOR scattering with the method of moments (MoM) for small appendages. The hybrid forumlation is discussed in detail, including an approximate Green’s function with permits the decoupling of the solutions from the FEM and the MoM. Numerical examples are given to show the applicability and accuracy of the hybrid technique.